Regulation of mutagenesis by exogenous biological factors in the eukaryotic cell systems - Lukash, L.L. (Вiopolymers and Cell, 2013)
The representations of the mutations and the nature of spontaneous mutation process and mutagenesis induced by exogenous oncoviruses, DNAs and proteins-mitogens are analysed. Exogenous biological factors induce DNA damages in regulatory-informational way, acting on the cellular systems for maintenance of genetical stability. Molecular mechanisms are the same as at spontaneous mutagenesis but they are realized with the participation of alien genetical material. Among biological mutagens, the oncoviruses and mobile genetic elements (MGEs) are distinguished as the strongest destabilizing factors which direct tumor transformation of somatic mammalian cells. Genetical reprogramming or changing the programs of gene expression at the differentiation of stem and progenitor cells under growth factors and citokines is probably followed by mutations and recombinations as well.